A Content Analysis of Update: Applications of Research in Music Education (1989–2017). (October 2019) - Silvey, Brian A.; Sims, Wendy L.; Pohlman, Gretchen; Regier, Bradley J.
We analyzed the article types, participants, and topics represented in Update articles published between 1989 and 2017 ( N = 379), beginning when MENC (now NAfME) took over publication of the journal. Quantitative research articles (46.42%) and literature reviews (28.84%) accounted for the largest portion of articles published. The percentage of qualitative research articles published has increased over time, while the percentage of historical articles and essays has decreased. Journal authors investigated a large variety of topics ( N = 68), with teaching methods and techniques (7.14%) and teaching students with exceptionalities (4.51%) representing the most frequent article topics. Authors most frequently recruited public school personnel, special populations, and college/university students as participants. These data provide insights into the article types, participants, and topics of interest in research designed to inform in-service music teachers, provide guidance for authors seeking publication venues, and help students and researchers know where to find various types of articles and topics.